A Study on Prescribing Patterns of Drugs in Geriatric Patients in a Tertiary Care Hospital: A Cross-sectional Study - Mydhily, S; Faiyza, Lubna; S Sharma, Pooja; VM, Uma; BD, Manikanta; KH, Dheeresh (Indian Journal of Pharmacy Practice)
Background: Rational drug use plays even more significant role in case of geriatrics as they are the majority of drug consumers compared to the rest of the population. Objectives: The main objectives of this study were to determine the prevalence of PIMs in geriatric prescriptions and to determine the association between number of PIMs prescribed with total number of drugs prescribed, number of comorbidities and age. Materials and Methods: The data of 110 patients who were all above 60 years of age were collected. And analysed and interpreted using google forms and IBM SPSS Statistics 28.0 version. In this study, prevalence of PIMs and the association between number of PIMs prescribed with total number of drugs prescribed, number of comorbidities and age will be determined. Results: Most prescriptions that is 22.7% prescriptions had 4 PIMs present. The correlation between number of drugs prescribed and number of PIMs is having medium positive correlation as R=0.570 and correlation between number of PIMs and Age is having low positive correlation as R=0.262 and correlation between number of PIMs and number of comorbidities is having medium positive correlation as R=0.317. Conclusion: The study revealed that the prescribing patterns in the hospital was irrational as there was at least one PIM present in each prescription that was studied. This study accentuates the fact that physicians and pharmacists must be made aware of guidelines or criteria like the Beers criteria to practise safer prescribing patterns in elderly.
Keywords: Beers criteria; Geriatrics; Potentially inappropriate medications (PIMs); Rational drug use; Polypharmacy